DEVELOPMENT OF THE DORMITORY NANNY PARENTING MODEL IN SHAPING THE MORALS OF STAI AS-SUNNAH DELI SERDANG STUDENTS - Nur Haflisma Lubis; Mardianto; Salminawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The development of female students in dormitories is an important part of Islamic education. However, the implementation of coaching in the STAI As-Sunnah Deli Serdang Student Dormitory still faces various obstacles, such as the lack of a structured parenting model, the lack of operational guidelines for musyrifah, and the discovery of various violations of rules that show that the process of moral formation is not optimal. This research aims to develop the STAI As-Sunnah Deli Serdang Student Dormitory Maintenance Module, analyze its development steps, and test the feasibility, effectiveness, and practicality of the resulting modules. The research uses the Research and Development (R&D) method with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques are carried out through observation, interviews, documentation, questionnaires, and tests. The feasibility of the product was validated by material experts, design/media experts, and linguists, while the effectiveness was tested using pre-test and post-test to 38 female students and analyzed with Normalized Gain (N-Gain). Practicality was measured through a questionnaire of musyrifah and female students. The results of the study show that the modules developed meet the criteria are very feasible based on the validation of experts. The effectiveness test showed an increase in the average score from 41 in the pre-test to 81 in the post-test with an N-Gain value of 0.68 (medium category), so that the module was effective in increasing students' understanding of Islamic morals. The practicality test also received a very positive response, with a percentage of 83% from musyrifah and 88% from female students. Thus, the STAI As-Sunnah Deli Serdang Dormitory Dormitory Maintenance Module is declared feasible, effective, and practical as a guideline for moral development in the dormitory environment.